TEST OF THE VALIDITY AND RELIABILITY OF THE SOCIAL STIGMATIZATION SCALE OF ATTITUDES TOWARDS PRISONERS (ATP) CORRECTIONAL CLIENTS - Rachmawati, Niken; Hamzah, Imaduddin (TOPLAMA, 2024)
One of the challenges in the correctional system is the negative stigma associated with clients and released inmates, making it difficult for inmates to integrate positively into society. Until now, there has been no method to assess the extent of the community's attitudes towards released or parolee inmates in a specific region. This research aims to test the validity and reliability of the Attitudes Towards Prisoners (ATP) scale in the Indonesian language. Developed by Melvin, the ATP scale has been validated and demonstrated good trial reliability, with excellent consistency when tested in various countries. The adaptation of this instrument involved steps such as Forward-Backward Translation, instrument panel testing based on translation results, instrument revisions, content validity, back translation, instrument approval, data collection, and instrument reliability. For testing the validity and reliability, the scale was distributed online using Google Forms to 224 respondents, including correctional groups, students, the general public, and correctional officers. The results of the ATP scale's validity test found that 35 items were valid, while 1 item was not valid, with a Cronbach's Alpha value of 0.917. The findings of this study recommend the use of the ATP as a supporting instrument in assessing the community's attitudes towards released inmates and further research in the field of inmate integration.